2019
DOI: 10.1002/jcla.22915
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of severity of asthma in children with body mass index, adiponectin and leptin

Abstract: BackgroundThis study aims to investigate the correlations of asthma in children with body mass index (BMI), adiponectin, and leptin.MethodsA total of 122 children with asthma in our hospital from January 2017 to February 2018 were randomly selected and divided into control group (normal) and observation group (BMI > 28 kg/m2) according to BMI. BMI, adiponectin, and leptin levels between the two groups were measured and compared, and correlations of disease grade with BMI, adiponectin, or leptin were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
15
0
5
Order By: Relevance
“…It seems that serum adiponectin levels would be related to asthma severity, especially in children [79]. Ma et al [80] analyzed serum adiponectin levels and BMI in 122 asthmatic children, concluding that asthma severity was negatively correlated with adiponectin levels, and positively correlated with BMI. These results are in concordance with previous studies showing that obese and asthmatic children presented an inadequate asthma control and lower serum levels of adiponectin when compared with non-obese asthmatic children [81,82].…”
Section: Anti-inflammatory Adipokines: Adiponectinmentioning
confidence: 99%
“…It seems that serum adiponectin levels would be related to asthma severity, especially in children [79]. Ma et al [80] analyzed serum adiponectin levels and BMI in 122 asthmatic children, concluding that asthma severity was negatively correlated with adiponectin levels, and positively correlated with BMI. These results are in concordance with previous studies showing that obese and asthmatic children presented an inadequate asthma control and lower serum levels of adiponectin when compared with non-obese asthmatic children [81,82].…”
Section: Anti-inflammatory Adipokines: Adiponectinmentioning
confidence: 99%
“…Although OSA is common in pediatric obesity and represents an independent risk factor for metabolic syndrome, an association, independent of excess weight, between Ad and OSA, oxygen desaturation, and percentage of time of sleep in this population could not be demonstrated [77]. However, a recent study performed in a small sample of Chinese children with asthma suggests an inverse correlation between Ad levels and the severity of the disease [78].…”
Section: Adiponectin Obesity and Metabolic Syndromementioning
confidence: 99%
“…In this study, leptin levels were significantly higher in obese and nonobese children with asthma compared to the healthy control group [17]. In the study of Ma et al, Serum leptin levels were measured in asthmatic and healthy children, and a positive correlation was reported between BMI and leptin levels [18]. In a study evaluating 138 children, it was reported that serum leptin levels were significantly higher in obese patients compared to normal weight individuals, and serum leptin levels were 2 times higher in obese patients with asthma compared to those who were obese and did not have asthma [19].…”
Section: Discussionmentioning
confidence: 42%